Corrosion‐Resistant and High‐Entropic Non‐Noble‐Metal Electrodes for Oxygen Evolution in Acidic Media. Issue 3 (7th December 2022) - Tajuddin, Aimi A. H.; Wakisaka, Mitsuru; Ohto, Tatsuhiko; Yu, Yue; Fukushima, Haruki; Tanimoto, Hisanori; Li, Xiaoguang; Misu, Yoshitatsu; Jeong, Samuel; Fujita, Jun‐ichi; Tada, Hirokazu; Fujita, Takeshi; et al.
Abstract: To realize a sustainable hydrogen economy, corrosion‐resistant non‐noble‐metal catalysts are needed to replace noble‐metal‐based catalysts. The combination of passivation elements and catalytically active elements is crucial for simultaneously achieving high corrosion resistance and high catalytic activity. Herein, the self‐selection/reconstruction characteristics of multi‐element (nonary) alloys that can automatically redistribute suitable elements and rearrange surface structures under the target reaction conditions during the oxygen evolution reaction are investigated. The following synergetic effect (i.e., cocktail effect), among the elements Ti, Zr, Nb, and Mo, significantly contributes to passivation, whereas Cr, Co, Ni, Mn, and Fe enhance the catalytic activity. According to the practical water electrolysis experiments, the self‐selected/reconstructed multi‐element alloy demonstrates high performance under a similar condition with proton exchange membrane (PEM)‐type water electrolysis without obvious degradation during stability tests. This verifies the resistance of the alloy to corrosion when used as an electrode under a practical PEM electrolysis condition. Abstract : Corrosion‐resistant non‐noble‐metal catalysts demonstrate the possibility of replacing noble metals such as IrO2 as anode catalysts in acidic media. The place replacement of Ni and Co as catalytically active elements in passivation elements such as Ti, Zr, Nb, and Mo plays an important role in enhancing oxygen evolution reaction activity.